Look Up (Again) The Apophis Asteroid: Simulating and Visualizing Orbit - Cahyo Puji Asmoro; Judhistira Aria Utama; Deni Karsa Sondana (Universitas Khairun, 2023)
The asteroid Apophis, first discovered in 2004 by American astronomers, is known to have a dangerous potential for planet Earth. Many early studies predict that in 2029 it will experience a close encounter and have a possible collision with the Earth at the next close encounter due to keyhole gravity. This research will explain how to carry out an orbit simulation using an orbit integrator to review this possibility and the evolution of the Apophis asteroid orbit over the next 500 years. The results of this study are expected to provide an understanding of simulating asteroid orbit from its orbital parameters and to build awareness of the threat of danger from small solar system objects such as asteroids, comets, and meteoroids.